2020
DOI: 10.3389/fbioe.2020.00369
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cell Morphology Regulates Inflammatory Cells Through MicroRNA Transferred by Extracellular Vesicles

Abstract: Vascular inflammation plays an important role in the pathogenesis and the development of cardiovascular diseases such as arteriosclerosis and restenosis, and the dysfunction of endothelial cells (ECs) may result in the activation of monocytes and other inflammatory cells. ECs exhibit an elongated morphology in the straight part of arteries but a cobblestone shape near the pro-atherogenic region such as branch bifurcation. Although the effects of hemodynamic forces on ECs have been widely studied, it is not cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The ability to generate microparticles is known for various cell types, including endothelial and myeloid cells [ 222 , 223 , 224 ]. Microparticles are now considered part of a complex mechanism of intercellular interaction and information exchange through the transfer of microRNAs and some proteins, including those thought to have functional activity [ 225 , 226 ]. Microparticles can be taken up by other cells and thus gain a biological link to the original cell.…”
Section: Lipid Metabolism Disorders In the Development And Progression Of Copdmentioning
confidence: 99%
“…The ability to generate microparticles is known for various cell types, including endothelial and myeloid cells [ 222 , 223 , 224 ]. Microparticles are now considered part of a complex mechanism of intercellular interaction and information exchange through the transfer of microRNAs and some proteins, including those thought to have functional activity [ 225 , 226 ]. Microparticles can be taken up by other cells and thus gain a biological link to the original cell.…”
Section: Lipid Metabolism Disorders In the Development And Progression Of Copdmentioning
confidence: 99%
“…Extracellular vesicle, as a nanovesicle secreted by various types of cells, encapsulates and transfers a wide range of functional proteins, lipids and nucleic acids to recipient cells to mediate intercellular communication [15]. Growing evidences indicated that EVparticipates in OSAS-or IH-associated cardiovascular diseases through transferring the altered EV components [16,17]. Landscape studies of EV-miRNA changes under OSAS or IH are bound to provide possible insights into the potential molecular mechanisms of IH-related cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…These studies are essential first steps to characterizing EVs derived from a specific cell line and their impacts on a defined recipient cell type, as current in vivo approaches are challenging due to the multiple cellular sources of EVs that may lack specific markers, tracking difficulties and complex biodistributions. The importance of physiological conditions was demonstrated when HUVECS were cultured on a poly-dimethyl siloxane membrane to create elongated endothelial cells, and it showed that EVs expressed from elongated endothelial cells suppressed the activation of monocytes via the upregulation of anti-inflammatory miRNAs [ 143 ]. When considering 2D and 3D models, it was demonstrated that 3D models better mimic in-vivo EV characteristics of size distribution and cargo [ 144 ].…”
Section: Experimental Approaches For the Study Of Ev And Ev-cell Interactionsmentioning
confidence: 99%